(untitled) (SAARC Journal of Agriculture, 2024)
Chinese citrus fly, Bactrocera minax, (Enderlin) (Tephritidae: Diptera) is univoltine pest causing severe damage in citrus fruits. Longivity in different carbohydrate diets and morphometrics of adult Chinese citrus fly (CCF) was studied in uncontrolled laboratory room in Agriculture and Forestry University, Chitwan, Nepal. The result showed that the emergence of CCF was the highest (88%) for the pupa weighing more than 0.076 g with male and female emergence ratio of 1:2.1 followed by pupal weight of 0.049-0.076 g with emergence of 82.1%. The maximum population emerged at the last week of March, 2021. The adult emergence was recorded 66-90% at the additional moisture content of 15-20% in oven-dried soil with no adult emergence in completely oven dried soil. The adult longivity was 17.90 ± 1.80 days for female adult in 10% sucrose solution and was 15.09 ± 1.49 days for male adult in 10% jaggery solution. Length of Chinese citrus fly pupa was 7.46 ± 0.30 mm while breadth was 0.97 ± 0.004 mm with average weight of 0.078 ± 0.002 g. Similarly, length of female was 16.09 ± 0.27 mm including ovipositor (4.28 ± 0.41 mm) which was 43.8% higher than male fly (11.39 ± 0.16 mm). Wing span of male was 2.50 ± 0.006 cm and of female was 2.72 ± 0.10 cm where female had 8.8% wider wing span compared to male. The study findings are useful in comparing characters of B. minax with other fruit fly species to develop the specific management practices of CCF. SAARC J. Agric., 22(1): 85-96 (2024)